Barriers and enablers to integrating maternal and child health services to antenatal care in low and middle income countries. (9th February 2016) - de Jongh, TE; Gurol‐Urganci, I; Allen, E; Jiayue Zhu, N; Atun, R
Abstract : Antenatal care (ANC) represents a delivery platform for a broad range of health services; however, these opportunities are insufficiently utilised. This review explores key barriers and enablers for successful integration of health s"ervices with ANC in different contexts. Data from peer‐reviewed and grey literature were organised using the SURE checklist. We identified 46 reports focusing on integration of HIV, tuberculosis, malaria, syphilis or nutrition services with ANC from Asia, Africa and the Pacific. Perspectives of service users and providers, social and political factors, and health system characteristics (such as resource availability and organisational structures) affected ease of integration. Tweetable abstract: Health system factors, context and stakeholders must be considered for integrated antenatal care services. Tweetable abstract: Health system factors, context and stakeholders must be considered for integrated antenatal care services.